(3abg GddZI hSQ GdYQHjIs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3QSGdI LYdgG YHO Gdedc Hf eMeO Hf ESeGYjd ebOeI dcJGH abg GddZI hSQ GdYQHjI hGdYQHjI NjQ GddZGJ hGdCdSfI hGdEbHGd Ydi JVegG ef GdOjGfI s
(3BNQgG (B:s
(3aUd ai JbSje GdRjGOI (B: (3CbeQ GdgdGd feG GdeGd eO GdeGA QHG GdHfJ RcG GdRQY QGY GdWYGe ef GdQHY hgh GdfRd Je GdcJGH s
(3HChdgG hBNQgG bQGAGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B176 s
Keywords: (3GddZIs